2020
DOI: 10.3390/su12083275
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Entrepreneurship in the Agriculture Sector: The Nexus of the Triple Bottom Line Measurement Approach

Abstract: The field of entrepreneurship is considered essential for the economy, and many researchers around the world have studied it from diverse perspectives. The outcomes of this research are not yet consensual. Today, it is gaining attention and consensus due to the increasing pressure of sustainable development, so there is a need for academic research to examine this field by incorporating sustainability value creation practices and the efforts of current entrepreneurs towards said goal, especially in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 88 publications
(137 reference statements)
10
77
0
5
Order By: Relevance
“…It can be inferred that acquisition of sustainable entrepreneurial education can enhance student’s self-efficacy and self-identity. In terms of the positive influence of sustainability attitude on SEI, the findings are in line with previous researches (Kalsoom, 2019; Liñán and Chen, 2009; Sargani et al , 2020), where authors found positive influence of attitude on entrepreneurship intention. Therefore, it can be deduced that Pakistani students’ attitude toward suitability can lead them to launch sustainable business ventures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It can be inferred that acquisition of sustainable entrepreneurial education can enhance student’s self-efficacy and self-identity. In terms of the positive influence of sustainability attitude on SEI, the findings are in line with previous researches (Kalsoom, 2019; Liñán and Chen, 2009; Sargani et al , 2020), where authors found positive influence of attitude on entrepreneurship intention. Therefore, it can be deduced that Pakistani students’ attitude toward suitability can lead them to launch sustainable business ventures.…”
Section: Discussionsupporting
confidence: 91%
“…Over the past few decades, the study of sustainability in entrepreneurship holds paramount position (Sargani et al , 2020; Fayolle et al , 2014; lakovleva et al , 2011; Usaci, 2015; Koe et al , 2014). The researchers have tried to administer different studies focusing on the sustainable entrepreneurship, but the area of sustainable entrepreneurship has been under-researched, especially in the developing markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also pertains to creating profitable enterprises and achieving certain environmental and social objectives; and pursuing and achieving what we often refer to as the triple bottom-line (Sarango-Lalangui et al, 2018). Scholars (Hussain et al, 2018;Sargani et al, 2020;Gu et al, 2020) have used the triple bottom line model to explain sustainable entrepreneurship. They developed it on the assumption that entrepreneurs should develop new "win-win-win" approaches.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that prior knowledge of both negative and positive trends, changes, and conditions can be influential on sustainable entrepreneurs' abilities to identify opportunities. Sargani et al (2020)' findings revealed a positive effect between sustainability attitudes and intention towards sustainable entrepreneurship in agriculture.…”
Section: Promoting Burundian Farmer Groups To Recognize Sustainable Omentioning
confidence: 92%